Let zeros or roots of a quadratic quadrilateral be a and b

Example: Form the quadratic polynomial whose zeroes or roots are 4 and 6.

Solution: **Sum of the zeroes** = 4 + 6 = 10**Product of the zeroes** = 4 × 6 = 24

Hence the polynomial formed by the given equation

= x^{2} – (sum of zeroes) x + Product of zeroes

= x^{2} – 10x + 24

Example: Form the quadratic polynomial whose zeroes are –3, 5.

Solution: Here, zeroes are – 3 and 5.**Sum of the zeroes** = – 3 + 5 = 2**Product of the zeroes** = (–3) × 5 = – 15

Hence the polynomial formed by

= x^{2} – (sum of zeroes) x + Product of zeroes

= x^{2} – 2x – 15

Example: Find a quadratic polynomial whose sum of zeroes and product of zeroes are respectively (i) , –1 (ii) √2, (iii) 0, √5

Solution: Let the polynomial be ax^{2} + bx + c and its zeroes be a and b.

(i) Here, α + β = ** **and α . β = – 1, therefore, the polynomial equation is formed by the formula

= x^{2} – (Sum of zeroes) x + Product of zeroes

= x^{2} – x – 1

The other polynomial are k.

If k = 4, then the polynomial is 4x^{2} – x – 4.

(ii) Here, α + β = √2 , α . β = . Thus the polynomial formed by

= x^{2} – (Sum of zeroes) x + Product of zeroes

= x^{2} – (√2) x + ** **

Other polynomial are k.

If k = 3, then the polynomial is 3x^{2} – 3√2x + 1

(iii) Here, α + β = 0 and α . β = √5, Thus the polynomial formed

= x^{2} – (Sum of zeroes) x + Product of zeroes

= x^{2} – (0) x + √5 = x^{2} + √5

Example: Find a cubic polynomial with the sum of its zeroes, sum of the products of its zeroes taken two at a time, and product of its zeroes as 2, – 7 and –14, respectively.

Solution: Let the cubic polynomial be ax^{3} + bx^{2} + cx + d, divide the whole polynomial by a, we get

⇒ x^{3} + x^{2} + x + ....(1) and its zeroes are a, b and g, then

a + b + g = 2 = –

ab + bg + ag = – 7 =

abg = – 14 = –

Putting the values of , and , in equtaion number 1, we get the cubic polynomial equation is

x^{3} + (–2) x^{2} + (–7)x + 14

⇒ x^{3} – 2x^{2} – 7x + 14

Example: Find the cubic polynomial with the sum, sum of the product of its zeroes taken two at a time and product of its zeroes as 0, –7 and –6 respectively.

Solution: Let the cubic polynomial be ax^{3} + bx^{2} + cx + d, then

⇒ x^{3} + x^{2} + x + ....(1) and its zeroes are a, b, g. Then

a + b + g = 0 = –

ab + bg + ag = – 7 =

abg = – 6 = –

Putting the values of , and ,, and in (1), we get

x^{3} – (0) x^{2} + (–7) x + (–6)

or x^{3} – 7x + 6

Example: If a and b are the zeroes of the polynomials ax^{2}+ bx + c then form the polynomial whose zeroes are and .

Solution: Since a and b are the zeroes of ax^{2} + bx + c

So a + b = , ab =

Sum of the zeroes = ** **+ =

= =

Product of the zeroes

= × ==

But required polynomial is given by the equation x^{2} – (sum of zeroes) x + Product of zeroes

⇒ x^{2} – x +

⇒ c

Example: If a and b are the zeroes of the polynomial x^{2}+ 4x + 3, form the polynomial whose zeroes are 1 + and 1 + .

Solution: Since a and b are the zeroes of the polynomial x^{2} + 4x + 3. Then, a + b = – 4, ab = 3

Sum of the zeroes

= 1 + ** **+ 1 + =

= = = =

Product of the zeroes

= (1 + )(1 + )= 1 + + + 1

= 2 + =

= ==

But required polynomial is given by the quadratic formula

x^{2} – (sum of zeroes) x + product of zeroes

or x^{2} – x + or k

or 3(if k = 3)

⇒ 3x^{2} – 16x + 16

If you want to give information about online courses to other students, then share it with more and more on Facebook, Twitter, Google Plus. The more the shares will be, the more students will benefit. The share buttons are given below for your convenience.

SHOW CHAPTERS